2017
DOI: 10.1177/000313481708300729
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Stage in Colon Cancer is Associated with Insurance Status

Abstract: Colorectal cancer continues to be the third most common cause of cancer death in the United States. Access to health care is also a nationwide problem. The purpose of the current study is to see if insurance status is associated with stage of colon cancer at presentation. The tumor registry was queried for all patients with colon cancer from 2009 to 2014. Demographics, including insurance status was statistically analyzed to determine if an association existed between insurance status and stage of colon cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The effectiveness of health insurance in influencing the stage of cancer detection and various other outcomes may also depend on the social determinants of a given population. 34 Other studies using state and hospital tumor registry data found associations between health insurance status and stage at diagnosis [35][36][37] ; however, these studies lacked multivariable analyses or were restricted to only 1 site, highlighting a need for more research examining this association across various population types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of health insurance in influencing the stage of cancer detection and various other outcomes may also depend on the social determinants of a given population. 34 Other studies using state and hospital tumor registry data found associations between health insurance status and stage at diagnosis [35][36][37] ; however, these studies lacked multivariable analyses or were restricted to only 1 site, highlighting a need for more research examining this association across various population types.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of this study was the ability to disentangle the associations among health insurance status, mode of detection, and stage at diagnosis, as most other studies on this topic have been unable to do. 14,15,32,[34][35][36] This disentanglement was possible because of our detailed approach to data collection. We used a highly structured computerassisted personal interview, informed beforehand by cognitive interviews with our patient population and administered by trained staff members employed by the University of Illinois at Chicago's Survey Research Laboratory.…”
Section: Strengths and Limitationsmentioning
confidence: 99%